Antibody screening reveals antigenic proteins involved in Talaromyces marneffei and human interaction - Wangsanut, Tanaporn; Amsri, Artid; Pongpom, Monsicha (Frontiers in Cellular and Infection Microbiology, 2023)
Talaromycosis is a fungal infection that generally affects immunocompromised hosts and is one of the most frequent systemic mycoses in HIV patients, especially in endemic areas such as Southeast Asia. Talaromyces marneffei, the causative agent of talaromycosis, grows as a mold in the environment but adapts to the human body and host niches by transitioning from conidia to yeast-like cells. Knowledge of the human host and T. marneffei interaction has a direct impact on the diagnosis, yet studies are still lacking. The morbidity and mortality rates are high in taloromycosis patients if the diagnosis and treatments are delayed. Immunogenic proteins are excellent candidates for developing detection tools. Previously, we identified antigenic proteins that were recognized by antibodies from talaromycosis sera. Three of these identified proteins have been previously characterized in detail, while the others have not been explored. To expedite the progress of antigen discovery, the complete list of antigenic proteins and their features was fully reported in this study. Functional annotation and Gene Ontology examination revealed that these proteins showed a high association with membrane trafficking. Further bioinformatics analyses were performed to search for antigenic protein characteristics, including functional domains, critical residues, subcellular localization, secretory signals, and epitope peptide sequences. Expression profiling of these antigenic encoding genes was investigated using quantitative real-time PCR. The results demonstrated that most genes were expressed at low levels in the mold form, but were highly upregulated in the pathogenic yeast phase, consistent with the antigenic role of these genes during the human-host interaction. Most transcripts accumulated in the conidia, suggesting a role during phase transition. The collection of all antigen-encoding DNA sequences described here is freely accessible at GenBank, which could be useful for the research community to develop into biomarkers, diagnostic tests, research detection tools, and even vaccines.